Identifikasi Faktor Penentu dalam Peningkatan Adopsi Benih Unggul Kakao oleh Petani - Dewi Listyati; Bedy Sudjarmoko; Abdul Muis Hasibuan (Jurnal Tanaman Industri dan Penyegar, 2015)
The productivity of smallholder cacao farmers is low due to the old plants and low adoption of superior seeds. The low adoption of superior seeds may be caused by multiple factors that are inter-related. This study aimed to assess factors that influenced farmers in the adoption of superior cacao seeds.  The study is important in formulating a strategy that would increase the adoption of cacao seeds by farmers. The research was conducted in two regenciess  of the cacao centre productions in Lampung Province (i.e. Pesawaran and North Lampung), from May to August 2012. The survey was conducted through a direct interview with 103 farmers in the study locations. Data on the respondences’s characteristics were analyzed descriptively.   Factors that may affect the adoption was analysed using a structural equation model (SEM). The results showed there were three most determining factors in the adoption of superior cocoa seeds, such as farmer’s preference, seed availability and external factors. Price of seeds was not an important factor in adoption of seeds. Hence, productivity, resistant to pests and diseases, productive age, fertilizer efficiency, ease of plant management, seed quality, seed vigor, availability/ease to access and dissemination method have important role to adoption process. The study implies that the strategy to increase seed adoption is providing superior cocoa seeds based on the farmers’ preference and establishing  the seed productions’s regions in the cocoa center production areas to ease of their accessibilities. In addition, the dissemination of information on the seeds superior characters should be promoted.